1992
DOI: 10.1136/thx.47.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Somnofluoroscopy, computed tomography, and cephalometry in the assessment of the airway in obstructive sleep apnoea.

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 19 publications
1
41
0
1
Order By: Relevance
“…In addition, the results obtained by static techniques such as cephalometry or CT scan do not provide information about UA dynamics. A discrepancy between static (lateral cephalometry, CT scan) and dynamic examinations of the UA (somnofluoroscopy) has been emphasized by PÉPIN et al [4]. These authors found an extension of airway collapse to the hypopharynx during somnofluoroscopy in 10 of 11 patients whereas CT scan did not show a reduction of this area in six of these patients.…”
mentioning
confidence: 72%
“…In addition, the results obtained by static techniques such as cephalometry or CT scan do not provide information about UA dynamics. A discrepancy between static (lateral cephalometry, CT scan) and dynamic examinations of the UA (somnofluoroscopy) has been emphasized by PÉPIN et al [4]. These authors found an extension of airway collapse to the hypopharynx during somnofluoroscopy in 10 of 11 patients whereas CT scan did not show a reduction of this area in six of these patients.…”
mentioning
confidence: 72%
“…The technique can produce lateral and transversal images as well as dynamic images of the craniofacial and upper airway anatomy [41]. More importantly, fluoroscopic images can be recorded during natural or drug induced sleep [40,42]. However it shares several limitations with cephalometric radiographs, including 2D analysis of 3D structures and exposure to ionizing radiation.…”
Section: Fluoroscopymentioning
confidence: 98%
“…is the most common SDB disorder with an estimated prevalence in the United States of America of 10% among [30][31][32][33][34][35][36][37][38][39] year old men, 17% among 50-70 year old men, 3% among [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year old women and 9% among 50-70 year old women [3]. OSAS is characterized by a recurrent partial or complete collapse of the upper airway during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Upper airway collapse is characteristic of OSA [46]. The overall mechanisms may be summarised as follows: ''upper airway collapse is initiated because the wakeful state provides compensatory neuronal activation of dilator muscles in an anatomically compromised collapsible pharynx; accordingly, when this activation is lost at sleep onset, the airway narrows and/or collapses'' [47].…”
Section: Upper Airway Collapsementioning
confidence: 99%